Does top executives' US experience matter? Evidence from US-listed Chinese firms - Jingjing Li; Minghai Wei; Bingxuan Lin (China Journal of Accounting Research, 2016)
Foreign firms face enormous obstacles in attracting investors and analysts when issuing securities in the United States. We use US-listed Chinese firms as our research sample and find that firms that hire top executives (i.e., Chief Executive Officer [CEO] or Chief Financial Officer [CFO]) with work experience in the US or educational qualifications from the US attract more US institutional investors and analysts. Further, we find that CFOs' US experience dominates the results. Corroborating our results, we further find that firms with US-experienced CFOs are more likely to hold conference calls and voluntarily issue management forecasts, which suggests that CFOs with a US background are better at communicating with US investors and analysts and acting in alignment with US norms compared with Chinese CFOs. Collectively, our results suggest that hiring a CFO with a US background could facilitate cross-listed foreign firms to lower US investors' and analysts' information disadvantage.
Keywords: 650; US-listed Chinese firms; Top executives' US experience; Analysts following; Institutional holdings